Knowledge, Attitudes, and Perceptions about Antibiotic Stewardship Programs among Neonatology Trainees - Kalu, Ibukunoluwa C.; Mukhopadhyay, Sagori; Dukhovny, Dmitry; Young, Rebecca; Guzman-Cottrill, Judith A. (American Journal of Perinatology, 2021)
Objective Antibiotic stewardship should be an essential component of neonatology training as neonatal intensive care units (NICU) have unique stewardship needs. Our aim was to assess neonatology fellowship trainees' knowledge, attitudes, and perceptions about antibiotic stewardship to inform sustainable curriculum development.Study Design We distributed an electronic survey to neonatology fellows in the United States over 4 months (January–April 2018) via Accreditation Council for Graduate Medical Education program directors.Results Of 99 programs in the United States with an estimated 700 fellows, 159 (23%) fellows from 52 training programs (53%) responded to the survey and 139 (87%) provided analyzed responses. Majority of respondents were training in southern (59; 42%) and northeastern (43; 31%) regions and were equally spread across all 3 years of training. One hundred (72%) respondents reported an antibiotic stewardship program (ASP) in their institution. While 86% (120/139) were able to identify the components of an ASP, 59% (82/139) either did not or were unsure if they had received antibiotic stewardship training during fellowship.Furthermore, while answering case studies, 124 (89%) respondents identified the optimal antibiotic for methicillin susceptible Staphylococcus aureus (MSSA) infection and 69 (50%) respondents chose appropriate empiric antibiotics for neonatal meningitis. Notably, fellowship training year was not significantly related to the proportion of incorrect knowledge responses (p = 0.40). Most survey respondents (81; 59%) identified small group sessions as the most useful teaching format, while others chose audit and feedback of individual prescribing behavior (52; 38%) and didactic lectures (52; 38%). Finally, ninety-five (69%) respondents preferred trainee-led ASP interventions targeting focal areas such as antifungal and surgical prophylaxis.Conclusion Antibiotic stewardship is a critical part of neonatology training. Neonatology fellows report variation in access to ASP during their training. Fellows prefer dedicated trainee-led interventions and stewardship curriculum taught within small group settings to promote targeted NICU ASP.Key Points
Keywords: antibiotic resistance; neonates; curriculum development